Sufism and Islam - Abdel-Karim, Gamal (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The Sufi experience is the encounter with absolute truth. This truth cannot be converted into a stronghold nor into a monopoly by and for anyone, and neither is it limited to a concrete culture, race or belief. According to the Sufi doctrine, man voluntarily offers himself in body and soul to God. Some ascetic and mystic sufis do so individually, while others, collectively, through retreats with mystical associations called turuq. Some sufis are members of associations as followers of a master (Shaykh) who allows them to live a normal and austere life compatible with specific norms and ascetic practices conforming to the criteria of each tariqa (way of mystical initiation). Sufism is thus converted into perfect Islam under the guidance of its experienced masters and spiritual guides (shuyukh), and into pious associations imparting sufi teachings and practices. Arabic-Moslem religiosity reaches its perfection in the mystical experience of Sufism, in which the human being, liberated from the deception of the immediate, offers himself to God and feels united to God who is like an immense light manifesting its greatness in the universe.
Keywords: sufism; Arabic-Moslem spirituality; Islamic asceticism; Islamic mysticism; Islam; Koran; interior life; interior cosmic experience